Functional Localization of Adult-Onset Idiopathic Nesidioblastosis. (7th October 2022) - Hercus, Jess C.; Pasha, Pouneh; Al Lawati, Sadiq; Kim, Peter; Mattman, Andre; Webber, Douglas; Thompson, David M.
Abstract : Nesidioblastosis is a rare pancreatic disorder involving enlarged beta cells throughout the pancreas, causing elevated insulin production. We present the case of a 53-year-old woman with the initial symptom of fasting hypoglycemia. No pancreatic lesions were indicated on computed tomography and magnetic resonance imaging scans, and an octreotide scan was negative for insulinoma. Selective arterial calcium stimulation (SACST) showed increased insulin production from the stimulation of 3 out of 5 arteries. The SACST results suggested a diagnosis of nesidioblastosis, which was confirmed by histopathology after a subtotal distal pancreatectomy. The patient has normal glucose tolerance after surgery with no further problems of hypoglycemia, indicating that this is a rare case of nesidioblastosis extending only partially through the pancreas.